Rhabdomyosarcoma with cutaneous presentation. - Lanoël, A.; Fain, A.; Cervini, B.; Merediz, J.; Bocian, M.; García Díaz, R.; Cordisco, M.R.; González, M.T.; Laterza, A.; Gallo, G.; Dávila, M.T.; Pierini, A.M. (European Journal of Pediatric Dermatology, 2009)
Rhabdomyosarcoma is the most frequent soft parts tumor in children under the age of 15 years but its cutaneous presentation form is extremely rare. Material and methods. A retrospective analysis was carried out of all patients with cutaneous rhabdomyosarcoma, aimed at knowing their evolution and response to treatment. Results. Between August 1988 and January 2005, we identified 353 cases of rhabdomyosarcoma, 15 of whom (4.2%) were patients who exhibited a cutaneous manifestation at the moment of diagnosis. The most frequent primary localization was the face (9 patients). With regard to the evolution, 6/15 patients did not continue their follow-up at our hospital. Of the 9 remaining cases, 5 died, 3 are free of disease and 1 is under treatment without relapses. Conclusions. It is important to consider this pathology in the event of tumors with a very fast growth and to differentiate them from other tumor diseases of infancy.